IN PURSUIT OF RADICAL INNOVATION: TRANSFORMATIVE COMPETENCIES AND COMPLEX ISSUES APPROACH - Kłeczek, Ryszard; Hajdas, Monika (Organizacja i Kierowanie, 2023)
The focal point in this paper are the teams’ competencies, which differentiate innovation projects’ outputs. We are particularly interested in which competencies are worth investing in and training to achieve radical innovation (RI) and we respond to research calls for further exploration of the nature of capabilities required for RI. We believe this issue is not adequately addressed in extant innovation scholarship, as previous studies focus on the complexity of innovation projects as their major quality and not on the complexity of issues the team is required to innovate within a project. We believe dealing with complex projects requires different skillsets than dealing with complex issues, and we elaborate on this argument in our conceptual paper. We derive arguments from established concepts of RI, the complexity of innovation projects, wicked problems literature, and competencies required to achieve RI as an output. We support the conceptual development with empirical insights derived from an illustrative example of five innovation projects, their various performance, and outcomes. Our main finding is that the complex issue perspective highlights transformative competency (TC), understood as the ability of a team to challenge the status quo of an initial task given, as crucial to be invested in and trained in innovation teams if RI is an expected output. Such a perspective extends previous findings, which suggested that the RI skillset consists of discovery, incubation, and acceleration. As a result of our study, we offer several theoretical and methodological implications and future research avenues related to innovation teams performance.